The Impact of Pavement Condition Index on Life Cycle Cost of Tiom-Kuyawage and Tiom-Balingga Road Sections in Lanny Jaya Regency - Yaro Wanimbo; Bahtiar Bahtiar; Bernathius Julison; Harmonis Rante; Dewi Ana Rusim (Journal of Social Research, 2025)
The Papua Mountains region has extreme geographical challenges that have an impact on the high need for road infrastructure maintenance. This study aims to analyze the relationship between the value of the Pavement Condition Index (PCI) and Life Cycle Cost (LCC), and to consider estimated inflation and net present value (NPV) as the basis for long-term budget planning. The study was conducted on the Tiom–Kuyawage (4.6 km) and Tiom–Balingga (2.7 km) roads in Lanny Jaya Regency. The PCI value in Tiom–Kuyawage has decreased significantly from 89.19 (2023) to 58.30 (2025), while Tiom–Balingga remains high at 87.44 (2025). The projected total maintenance cost for 20 years (2025–2045) shows a need of IDR 201.42 billion for Tiom–Kuyawage and IDR 122.62 billion for Tiom–Balingga. However, if calculated based on present value (NPV), assuming inflation of 3.09% and an interest rate of 5.04%, the actual need will be IDR 105.75 billion and IDR 64.58 billion, respectively. These findings suggest that the deterioration of road conditions (PCI) directly raises the cost of maintenance (LCC), and that the use of an NPV-based financial approach is important for budget efficiency. This study recommends a road maintenance strategy based on actual conditions, to be carried out periodically in the mountainous Papua region.